Faktor Risiko Prenatal Perinatal Dan Postnatal Pada Kejadian Cerebral Palsy - Bambang Trisnowiyanto; Yohanes Purwanto (Poltekkes Kemenkes Surakarta, 2019)
Background: Cerebral Palsy (CP) is a disability disorder motor motorization is most common in children with a prevalence of 2-3 per 1000 live births. The term CP is explained as a group of movement and posture disorders that are often accompanied by impaired sensation, perception, cognition, communication, behavior, epilepsy, and secondary disorders of the musculoskeletal system. Disorders of CP occur in the immature central nervous system with non-progressive traits occurring in the prenatal, perinatal, and postnatal period. Methods: The purpose of this study is to determine how much prenatal risk factors, perinatal, and postnatal events in CP at the Kitty Center Clinic in Jakarta for 5 year (2013 - 2017). Result: An observational descriptive study, which described prenatal perinatal, and postnatal risk factors for CP events at the Kitty Center Clinic in Jakarta for a period of 5 years (2013-2017) with a total of 523 study subjects. Based on the analysis of data obtained, based on the type of CP 35% quadripelgia spastic, 36% spastic diplegia, 6% spastic hemiplegia, 9% athetosis, and 14% hypotonia. Based on sex 62% are men, and 38% are women with a ratio of 1.6: 1.0. Based on the age of the child 11% <2 years, 34% 3-6 years, 33% 7-12 years, and 22%13-18 years. Conclusion: Based on risk factors of 62% prenatal, 25% perinatal, and 12% postnatal. Prenatal risk factor is the biggest risk factor as much as 62% which causes Cerebral Palsy at the Kitty Center Clinic in Jakarta.